EXAMINING THE PRINCIPLES OF CLT APPROACH THROUGH HIGHER SECONDARY LEVEL ENGLISH TEXTBOOK IN BANGLADESH - Toshi Chakma (UICELL, 2021)
Textbook plays a significant role in the field of English Language learning and teaching in Bangladesh. English For Today is the textbook for higher secondary level (Grade 11 & 12) which is designed by the NCTB (National Curriculum and Textbook Board) on the basis of communicative approach. Based on the previous studies, it is assumed that though the textbook is designed under the principles of Communicative Language Teaching (CLT), it has failed to meet the demands of the learners and teachers in terms of bringing communicative competency. Keeping this issue in mind, the study aims to examine the textbook through in-depth analysis using the criteria from CLT. Qualitative descriptive analysis was used for this study to analyses the textbook in terms of how communicative, authentic and meaningful it is and whether it is accuracy or fluency oriented. The findings of the study reveal that most of the activities of the textbook do not reflect the principles of CLT approach which limits the student’s freedom of practicing all the language skills and as a result they end up being incompetent communicator. Finally, the paper concludes with some recommendations for the authorities to bring necessary changes in the activities and contents of the textbook in order to be an effective tool for both the language learners and teachers. Keywords: Communicative Language Teaching (CLT) Principles, HSC, English For Today, Activities in the Textbook